Analisis Pembelajaran Pendidikan Agama Islam pada Pendidikan Nonformal Program Paket C - Diah Mutiara; Siti Rohmah; Alvan Firdaus (UIN Sunan Gunung Djati Bandung, 2022)
The problem of this research is learning Islamic Education on education nonfomal program package C in Pusat Kegiatan Belajar Masyarakat (PKBM) Mitra Buruh Nusantara. Research aims to analyze learning religious education Islam in nonformal education package C in Pusat Kegiatan Belajar Masyarakat (PKBM) Mitra Buruh Nusantara. Research methodology used in the method descriptive qualitative. Procedure this research through interviews with a tutor Islamic education and observation on the learning Islamic education. This research result indicates: 1) Competence tutor religious education Islam in nonformal education Progam Packaege C in PKBM have not been in accordance with competence educator the requisite, 2) To overcome competence tutor that was still quite or less should tutor the training to increase competence.